Afetividade na educação superior a distância: com a palavra os estudantes de pedagogia - Pereira, Ana Lúcia (2017)
The present study was motivated by great concern of this researcher, who, after six years working as a college professor in classroom courses, had to face the challenge of teaching in distance learning (EaD). The core of such concern was on facing challenges in order that the established interactions with the students through virtual learning environments (AVA) could promote teaching and learning processes. The general objective of the present study was to “ascertain distance learning Pedagogy students’ perception on the role of affectivity in the interactions developed throughout the course”, and it was guided by the following research question: How is affectivity developed in a distance learning Pedagogy course, according to the students’ perception? The students who participated in the research attended a distance learning Pedagogy course in a large private institution, and a professor from the same institution participated as well. We chose the qualitative research approach and the theory of Wallonian Psychogenetics to support the data analysis. The collection of data followed three steps: (1) distribution of questionnaires to Pedagogy students in distance learning, which resulted in 134 answers; (2) semistructured interviews with eight students from the group that answered the questionnaire; (3) semistructured interview with the professor. We used techniques of Descriptive Statistics to analyse the data collected through the questionnaire. In order to analyse the interviews, we were inspired by prose analysis, proposed by André (1983). The analysis allowed us to realize that affectivity had been present since the moment the students chose Pedagogy course and distance learning, and throughout the course, it went on guiding the relationships established with professors, tutors, course mates, as well as with the course, the University and themselves. Among the feelings of positive nuances that they related, we highlight admiration, affection, appreciation, calmness, enthusiasm, happiness, gratitude, satisfaction and security. Among the feelings of negative nuances, which were mostly concerned to the University, we highlight anguish, regret, disappointment, frustration, insecurity and worry. Among the main results, we point out that the students’ feelings towards the professors are related to their own way to tape the videoclasses, which, in some cases, appeared as an important factor to level interest and motivation towards the subjects. Therefore, as to the professors, we can say that, according to the interviewed students, the feeling of affectivity arose from the videoclasses. Despite some criticism, in general, the students were optimistic about their course and the support they received in order to work as teachers in the future. They related feelings such as hope, happiness, pleasure and pride